Pertumbuhan anakan kepiting bakau (Scylla spp.) yang diberi pakan campuran buah pepaya mentah dan ikan Layang (Decapterus sp.) - Pattiasina, Bethsy J.; Pattipeiluhu, Shelly M.; Loupatty, Joice W.; Pattinasarany, Agapery Y.; Jamal, Endang (University of Pattimura, 2024)
Mud crab (Scylla spp.) is one of the coastal fisheries resources that has important economic value. Along with the increasing market demand for mud crabs, the development of mud crab aquaculture is widely practiced in various coastal areas in Indonesia. The availability of local resource-based feed is one of the key factors for the efficiency of aquaculture efforts and the sustainability of mangrove crab aquaculture production in the region. This study aimed to examine the effect of a combination of unripe papaya fruit and fish flesh (Decapterus sp.) with different ratios on the growth of young mud crab cultured using the floating raft method in the Tuhaha Bay waters, Tuhaha Village, East Saparua District. A total of 12 mud crab were fed a mixture of papaya and fish at 10% per total body weight per day. Treatment A (5% papaya: 5% fish flesh) and treatment B (7.5% papaya: 2.5% fish flesh) were given to six individual mud crabs each. Weight measurements were taken weekly during the one-month study period. The results showed that young mud crab fed treatment B tended to have higher absolute weight growth rate and specific growth rate compared to juvenile mud crab fed treatment A but were not statistically significantly different. This finding explains that the composition of 25%-50% unripe papaya fruit combined with fish flesh (Decapterus sp.) effectively increases the growth rate of the mud crabs.